Pengaruh Iklim Organisasi terhadap Organizational Citizenship Behavior pada Pegawai Badan Penanggulangan Bencana Daerah Kota Padang - Ibadullah Poeni, Muhammad Abiyu; Guspa, Anindra (YASIN, 2025)
The purpose of this study was to determine the effect of Organizational Climate on Organizational Citizenship Behavior at the Padang City Regional Disaster Management Agency. This study uses quantitative research methods, with sample techniques using total sampling, with a total of 68 subjects, the scale used in this study is a Likert scale. The results showed that Organizational Climate affects Organizational Citizenship Behavior by 0.086 (8.6%). This illustrates that the Organizational Climate variable affects Organizational Citizenship Behavior in employees by 8.6%, where the remaining 91.4% of the influence is influenced by other variables not examined in this study. It can be concluded that if the organizational climate in an organization is high, then OCB will also be high, and vice versa.